Enhanced access and isolation by simple modifications of dental armamentarium - Rajatha V Shetty; Sherin Geevarghese; Stuti; Rhea S Mathew; Shruthi Nagaraja (Wolters Kluwer Medknow Publications, 2022)
A good armamentarium facilitates the efficient working of the dentist which in turn improves the quality of treatment rendered to the patient. The present invention of the unit consisting of the flexible mirror attached to the suction and the dual suction tip aims at improving the clinical efficiency of dental treatments provided. This compact unit is designed to improve the visualization and isolation of the operating field. It is also easy to fabricate and alleviates the very relevant shortcomings of clinical work.